Linking Business Strategies to ESG Practices - Mazzioni, Sady; Soares, Víctor Frillich; Soschinski, Caroline Keidann; Vogt, Mara; Beuren, Ilse Maria (Journal of Posthumanism, 2025)
Stakeholders have been pressuring companies to adopt effective Environmental, Social, and Governance (ESG) practices. To understand corporate engagement beyond financial aspects, this study draws on the business strategies of Miles and Snow (1978). The article analyzes the influence of the prospector business strategy on the ESG practices of publicly traded Brazilian companies. In the archival research, data were collected from 2015 to 2023, totaling 2,154 observations, which were analyzed using Tobit regression, with industry fixed effects controlled and standard errors estimated robust to heteroskedasticity. The results indicate that companies with a more innovative and exploratory profile (prospectors) tend to exhibit better performance in ESG practices, especially in governance. The research findings contribute to managerial literature and business practice by providing insights for reflecting on business strategies and the incorporation of ESG practices that are more closely aligned with their strategic profiles.